Institutional conditions for the implementation of sustainable development on the example of self-governing agricultural bodies in Poland - Walkowiak, Katarzyna (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: The need for balance in the social, environmental and economic developments has been explored by numerous academic disciplines and fostered the implementation of subsequent political agendas both at the global and local levels. The 2030 Agenda for Sustainable Development adopted by the United Nations in 2015 is an example of an international initiative for sustainable development. All the goals of the Agenda were determined in view of global civilizational challenges, but in order for them to be implemented various stakeholders have to be involved, and projects on a national, regional, and local scale have to be carried out. Given the postulate of creating multilateral public and public-private partnerships for sustainable development and the principle of subsidiarity, it seems important to take into account the role of self-governing agricultural bodies in the system, implementing sustainable development goals. Agricultural self-governance is exercised in Poland through agricultural chambers established as public-law associations, forming part of the institutional system of public administration. The scope of tasks performed by these agricultural chambers covers matters of agriculture and rural development, including sustainable development. Aim: In her study the author seeks to answer the questions of whether the self-governing agricultural bodies in Poland are the key entities in the implementation of the postulates of sustainable development, or whether the competences of these agricultural chambers allow them to fully use the social potential of farmers for the dissemination of the concept of sustainable development. Results: The results of the survey demonstrate that the self-governing agricultural bodies play only a superficial role in the implementation of the sustainable development postulates. Although these agricultural chambers are formally established in the public law system, they do not have sufficient executive power, or material, human and financial resources to engage in effective action. The potential of the self-governing agricultural bodies to achieve the goals of sustainable development is not being fully used.